ChemInform Abstract: Thiazole‐Induced Rigidification in Substituted Dithieno‐Tetrathiafulvalene: The Effect of Planarisation on Charge Transport Properties. Issue 37 (September 2015) - Taylor, Rupert G. D.; Cameron, Joseph; Wright, Iain A.; Thomson, Neil; Avramchenko, Olena; Kanibolotsky, Alexander L.; Inigo, Anto R.; Tuttle, Tell; Skabara, Peter J.
Abstract Novel tetrathiafulvalene (TTF) containing compounds (III) are obtained by four‐fold Stille coupling between tetrabromo‐dithieno TTF (I) and stannylated thiophene (IIa) or thiazole (IIb).